Clinical Associations of Bitter Taste Perception and Bitter Taste Receptor Variants and the Potential for Personalized Healthcare - Mao Z; Cheng W; Li Z; Yao M; Sun K (Dove Medical Press, 2023)
Ziwen Mao,1,2 Weyland Cheng,1,2 Zhenwei Li,2 Manye Yao,2 Keming Sun2 1Henan Provincial Key Laboratory of Children's Genetics and Metabolic Diseases, Children's Hospital Affiliated to Zhengzhou University, Henan Children's Hospital, Zhengzhou Children's Hospital, Zhengzhou, Henan, People's Republic of China; 2Department of Orthopaedic Surgery, Children's Hospital Affiliated to Zhengzhou University, Henan Children's Hospital, Zhengzhou Children's Hospital, Zhengzhou, Henan, People's Republic of ChinaCorrespondence: Weyland Cheng, Henan Provincial Key Laboratory of Children's Genetics and Metabolic Diseases, Children's Hospital Affiliated to Zhengzhou University, Henan Children's Hospital, Zhengzhou Children's Hospital, 33 Longhu Waihuan East Road, Zhengzhou, Henan, People's Republic of China, Tel +86 18502758200, Email wey_c@hotmail.comAbstract: Bitter taste receptors (T2Rs) consist of 25 functional receptors that can be found in various types of cells throughout the human body with responses ranging from detecting bitter taste to suppressing pathogen-induced inflammation upon activation. Numerous studies have observed clinical associations with genetic or phenotypic variants in bitter taste receptors, most notably that of the receptor isoform T2R38. With genetic variants playing a role in the response of the body to bacterial quorum-sensing molecules, bacterial metabolites, medicinal agonists and nutrients, we examine how T2R polymorphisms, expression levels and bitter taste perception can lead to varying clinical associations. From these genetic and phenotypic differences, healthcare management can potentially be individualized through appropriately administering drugs with bitter masking to increase compliance; optimizing nutritional strategies and diets; avoiding the use of T2R agonists if this pathway is already activated from bacterial infections; adjusting drug regimens based on differing prognoses; or adjusting drug regimens based on T2R expression levels in the target cell type and bodily region.Keywords: bitter taste receptors, TAS2R38, chronic rhinosinusitis, obesity, oral health, cancer